Beyond non-regression: Mainstreaming climate action into FTAs - Emily Lydgate (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2023)
While integrating climate objectives into FTAs remains unusual, it is an area of rapid innovation. This chapter focuses on EU and New Zealand, both of whom have used FTAs to support climate-related goals. The EU has increased the enforceability of requirements to uphold the Paris Agreement and domestic climate regulation, while New Zealand has used FTAs to further regulatory cooperation, emphasizing fossil fuel subsidy reform. The UK also features in the analysis as a country that has completed recent FTAs with both. Innovative FTA provisions between countries who self-identify as climate leaders may appear limited in their scope and influence: outliers rather than frontrunners. However there is evidence to suggest they have already contributed to broader climate cooperation, and can do so further, by: propelling discussion other fora, including the WTO and Paris Agreement; addressing technical challenges for climate cooperation across different regulatory systems; breaking down silos between trade and climate agreements; and furthering a learning process about effective models for achieving climate cooperation through trade.
Keywords: 330; Climate change; Free Trade Agreements; climate cooperation; trade and environment